Estudo da variabilidade da precipitação e vazão na Bacia do Rio Iguaçu associada a anomalia de temperatura da superfície do mar no Oceano Pacífico Equatorial - Sousa, Patrícia de (2013)
The Iguaçu River basin is located between the States of Paraná and Santa Catarina, between the coordinates 25° 05 ' S 26° 45 ' S latitude and 48° 57 ' W 54° 50 ' W longitude. The Iguazu River is formed by the meeting of the rivers Irai Atuba, its sources and are located on the western edge of Serra do Mar, in the Curitiba metropolitan area. From its source to the mouth, the Iguaçu River has a length of approximately 1,092 km, flowing from East (Curitiba) to West (Foz do Iguaçu). The proposals of this work were the analysis of the structure and variability of rainfall in different scales in the basin of the Iguaçu and Paraná State. The study period was from 1980 to 2010. The historical series of precipitation and flow were provided by the national water agency (ANA), the Instituto Agronômico do Paraná (IAPAR) and by the supervision of Water resources development and environmental health (SUDERHSA). In this work we analyzed the data of precipitation in different scales (annual, interannual, seasonal and daily). The flow data were analysed in annual and interannual scale. From the data statistical analyses were performed using several statistical parameters (average, standard deviation, coefficient of variation and anomaly). The regionalization of rainfall was determined by Multivariate Analysis. Interannual variability was studied between precipitation and the anomaly of sea surface temperature, as well as to the flow. It was determined the rainfall anomaly index and the erosividade potential of the rain in the basin, especially in extreme events. Was also analyzed the correlation between rain and precipitation anomaly of sea surface temperature. In the region between the lower and the middle course was observed the highest volume of rainfall with values between 1860 to 2080 mm distributed between 105 to 111 days. These values decrease in opposite directions, i.e. decreases toward the downstream and upstream